Collocations of effective and efficient in COCA: A corpus analysis - Deliana; Gultom, Amanda Fransisca (International Journal of Culture and Art Studies, 2025)
This corpus-based study analyses two adjectives often perceived as synonymous, effective and efficient, by examining their collocations and formality levels in the Corpus of Contemporary American English (COCA). A qualitative content analysis was applied to 400 concordance lines, evenly divided between the two adjectives. The analysis involved selecting content, categorising data, developing coding rules, coding texts, and interpreting results. Collocational structures such as adjective + preposition, adjective + to-infinitive, adjective + that-clause, adverb + adjective, and adjective + noun were identified. The findings show that effective frequently collocates with nouns related to outcomes and appears predominantly in formal contexts, especially academic writing. In contrast, efficient commonly collocates with nouns related to processes and is used more flexibly across genres, including blogs and magazines. Grammatically, effective often combines with the prepositions in and at, while efficient shows greater variety and frequently occurs in to-infinitive and that-clause constructions. The study concludes that effective and efficient have distinct collocational patterns, grammatical behaviours, and degrees of formality, making them not fully interchangeable in all contexts.